DECISION SUPPORT SYSTEM FOR DETERMINING BEST HOMEROOM TEACHER WITH TOPSIS METHOD IN MIS NURUL HUDA PANTAI LABU - Purba, Elisa; Vinsensia, Desi; Utami, Yulia (ZERO: Jurnal Sains, Matematika dan Terapan, 2018)
During this time the determination of the best homeroom teacher at MIS Nurul Huda Pantai Labu  was still using a manual process , so the results were not optimal. In this study the  decision support system was built to facilitate the school in determining the best homeroom teacher using the Topsis method. The criteria used are 5: attendance, organizational experience, data on student achievement, interaction with students, and final education. This system design application is expected to help the school principal in making decisions about determining the best homeroom teacher